Uncovering and Engineering a Mini-Regulatory Network of the TetR-Family Regulator SACE_0303 for Yield Improvement of Erythromycin in Saccharopolyspora erythraea - Liu, Ying; Khan, Sabir; Wu, Panpan; Li, Bowen; Liu, Lanlan; Ni, Jingshu; Zhang, Hongxia; Chen, Ketao; Wu, Hang; Zhang, Buchang (Frontiers in Bioengineering and Biotechnology, 2021)
Erythromycins produced by Saccharopolyspora erythraea have the broad-spectrum antibacterial activities. Recently, several TetR-family transcriptional regulators (TFRs) were identified to control the erythromycin production by multiplex control modes; however, their regulatory network remains poorly understood. In this study, we report a novel TFR, SACE_0303, positively correlated with the erythromycin production in Sac. erythraea. It directly repressed its adjacent gene SACE_0304 encoding a MarR-family regulator, but indirectly stimulated erythromycin biosynthetic gene eryAI and resistance gene ermE. SACE_0304 negatively regulated the erythromycin biosynthesis by directly inhibiting SACE_0303 as well as eryAI and indirectly repressing ermE. Then, the SACE_0303 binding site within the SACE_0303-SACE_0304 intergenic region was defined. Through genome scanning combined with in vivo and in vitro experiments, three additional SACE_0303 target genes (SACE_2467 encoding cation-transporting ATPase; SACE_3156 encoding a large transcriptional regulator; SACE_5222 encoding α-ketoglutarate permease) were identified and proved to negatively affect the erythromycin production. Finally, by coupling CRISPRi-based repression of those three targets with SACE_0304 deletion and SACE_0303 overexpression, we performed stepwise engineering of the SACE_0303-mediated mini-regulatory network in a high-yield strain, resulting in enhanced erythromycin production by 67%. In conclusion, the present study uncovered the regulatory network of a novel TFR for control of erythromycin production and provided a multiplex tactic to facilitate the engineering of industrial actinomycetes for yield improvement of antibiotics.